(untitled) (Indonesian Theological Justice Review, 2024)
Indigenous communities in Indonesia have long faced marginalization, land dispossession, and discrimination. This paper explores the intersection of religious justice and indigenous rights, focusing on how theology can support the struggles of indigenous communities for recognition, land rights, and cultural preservation. Drawing on Islamic, Christian, and indigenous theological perspectives, the study examines how religious teachings on justice, equality, and stewardship of the earth can be applied to address the social, cultural, and political challenges faced by indigenous peoples in Indonesia. The paper highlights theological concepts such as the Islamic notion of human dignity (karamah) and the Christian emphasis on justice for the oppressed, while also considering the role of indigenous beliefs in protecting their lands and traditions. The research emphasizes the potential of religious communities to advocate for the rights of indigenous peoples, both within religious frameworks and in the broader legal and political context. The paper argues that religious leaders and communities can play a crucial role in advancing indigenous rights by using theological arguments to challenge injustice and promote reconciliation. Recommendations include promoting interfaith advocacy for indigenous rights, educating religious communities about indigenous struggles, and fostering collaboration between indigenous groups and religious organizations.